Policy Diffusion of Environmental Performance: Economic and Institutional Determinants in Emerging Markets - Ika Sulistyawati, Ardiani; Himmawan Dwi Nugroho, Arief (Analisis Data Innovation, 2024)
Purpose – We investigate major economic and institutional determinants of environmental policy diffusion among emerging markets in this study.Design/methodology/approach – Using panel data from 15 emerging markets and applying a fixed-effects regression model and Granger causality tests, this analysis investigates the determinants of environmental performance of emerging economies in relation to economic growth, investment in the environment, institutional quality, international pressure and public awareness. EPI, IEA, United UNEP.Findings – The outcomes indicate that institutional quality and public awareness of improving environmental performance has a significant impact, while economic growth and investment environment also play a furthering role. However, external pressure is a context-limited, variable, constraining force. They suggest institutional strength and public involvement matter more than outside pressure to explain which policies stick.Originality/value – This study develops novel insights into the mechanisms of environmental policy diffusion by integrating the economic and institutional perspectives. It underscores the need for governance reforms, public engagement, and economic alignment to speed up sustainability progress.Research Implications – The study emphasises that policymakers need to focus on institutional development, informed public participation and targeted economic policies to improve environmental outcomes. Future research should explore the role of transnational cooperation and sector-specific policies in promoting sustainability.